The Role of Talent Pools in Reducing Talent Derailment: An Analytical Study of the Views of a Sample of Employees at the University of Kufa - Kareem, Amer; Obaid, Hayder; Yasir, Mohanad (The Arab Journal of Administration, 2020)
This Research aims to identify the Relationship and Impact between the Talent Pools through its Dimensions (Organizational citizenship behavior, organizational trust, staff turnover) and Talent Derailment through its Dimensions (human relationships, inability to build teams, inability to adapt, narrow career orientation, failure to achieve business objectives). The research problem identified a major question as to whether there is a role for the Talent Pools in the departments and units of the organization to limit the deviation of these talents in the work environment, and for this to develop a hypothesis for research that translates the main hypothesis and the subsidiary hypotheses. The research was used as a means of obtaining data. The Research community was the administrative and financial departments in the presidency of the University of Kufa. The entire research community was targeted, with (67) Employees and (53) Questionnaires valid for analysis. The data were analyzed using a set of statistical methods and results were extracted using SPSS v.20. The research reached a number of conclusions and recommendations, such as that the organization should strive to retain talents and develop them in all departments of the university and work to face the biggest challenge of diversifying these Talents in the Organizational work Environment and working on their Development on objective basis, Management of Talent in Organizations.